At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's find the zeroes of each quadratic polynomial and verify the relationship between the zeroes and the coefficients.
### (i) [tex]\( x^2 - 2x - 8 \)[/tex]
1. Find the zeroes:
The quadratic equation is [tex]\( x^2 - 2x - 8 = 0 \)[/tex]. To find the zeroes, we solve:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = -2 \)[/tex], and [tex]\( c = -8 \)[/tex].
Solving, we get:
[tex]\[ x = \frac{2 \pm \sqrt{4 + 32}}{2} = \frac{2 \pm 6}{2} \][/tex]
So, the zeroes are:
[tex]\[ x = \frac{2 + 6}{2} = 4 \quad \text{and} \quad x = \frac{2 - 6}{2} = -2 \][/tex]
Thus, the zeroes are [tex]\( x = 4 \)[/tex] and [tex]\( x = -2 \)[/tex].
2. Verify the relationship between the zeroes and coefficients:
- The sum of the zeroes ([tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]) of [tex]\( ax^2 + bx + c = 0 \)[/tex] should be [tex]\( -\frac{b}{a} \)[/tex]:
[tex]\[ \alpha + \beta = - \frac{b}{a} = -\frac{-2}{1} = 2 \][/tex]
Here, the sum is [tex]\( 4 + (-2) = 2 \)[/tex], so it matches.
- The product of the zeroes ([tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]) should be [tex]\( \frac{c}{a} \)[/tex]:
[tex]\[ \alpha \beta = \frac{c}{a} = \frac{-8}{1} = -8 \][/tex]
The product is [tex]\( 4 \times (-2) = -8 \)[/tex], so it matches.
So, for [tex]\( x^2 - 2x - 8 \)[/tex]:
- Zeroes: [tex]\( 4 \)[/tex] and [tex]\( -2 \)[/tex]
- Sum of zeroes: [tex]\( 2 \)[/tex]
- Product of zeroes: [tex]\( -8 \)[/tex]
### (ii) [tex]\( 4s^2r^4 + 4s + 16 \)[/tex]
1. Find the zeroes:
The quadratic equation is [tex]\( 4s^2r^4 + 4s + 16 = 0 \)[/tex].
Solving for [tex]\( s \)[/tex]:
[tex]\[ s = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 4r^4 \)[/tex], [tex]\( b = 4 \)[/tex], and [tex]\( c = 16 \)[/tex].
Solving, we get:
[tex]\[ s = \frac{-4 \pm \sqrt{16 - 256r^4}}{8r^4} = \frac{-4 \pm \sqrt{4(1 - 16r^4)}}{8r^4} = \frac{-4 \pm 2\sqrt{1 - 16r^4}}{8r^4} = \frac{-2 \pm \sqrt{1 - 16r^4}}{4r^4} \][/tex]
So, the zeroes are:
[tex]\[ s = \frac{-2 + \sqrt{1 - 16r^4}}{4r^4} \quad \text{and} \quad s = \frac{-2 - \sqrt{1 - 16r^4}}{4r^4} \][/tex]
Thus, the zeroes are:
[tex]\[ \left( \frac{-\sqrt{1 - 16r^4} - 1}{2r^4}, \frac{\sqrt{1 - 16r^4} - 1}{2r^4} \right) \][/tex]
### (iii) [tex]\( 6x^2 - 3 - 7x \)[/tex]
1. Find the zeroes:
The quadratic equation is [tex]\( 6x^2 - 3 - 7x = 0 \)[/tex]. Rearranging it to standard form, we get [tex]\( 6x^2 - 7x - 3 = 0 \)[/tex].
Here, [tex]\( a = 6 \)[/tex], [tex]\( b = -7 \)[/tex], and [tex]\( c = -3 \)[/tex].
Solving, we get:
[tex]\[ x = \frac{7 \pm \sqrt{49 + 72}}{12} = \frac{7 \pm \sqrt{121}}{12} = \frac{7 \pm 11}{12} \][/tex]
So, the zeroes are:
[tex]\[ x = \frac{7 + 11}{12} = \frac{18}{12} = \frac{3}{2} \quad \text{and} \quad x = \frac{7 - 11}{12} = \frac{-4}{12} = -\frac{1}{3} \][/tex]
Thus, the zeroes are [tex]\( x = \frac{3}{2} \)[/tex] and [tex]\( x = -\frac{1}{3} \)[/tex].
2. Verify the relationship between the zeroes and coefficients:
- The sum of the zeroes ([tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]) should be [tex]\( -\frac{b}{a} \)[/tex]:
[tex]\[ \alpha + \beta = - \frac{b}{a} = -\frac{-7}{6} = \frac{7}{6} \][/tex]
Here, the sum is [tex]\( \frac{3}{2} + \left(-\frac{1}{3}\right) = \frac{9}{6} - \frac{2}{6} = \frac{7}{6} \)[/tex], so it matches.
- The product of the zeroes ([tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]) should be [tex]\( \frac{c}{a} \)[/tex]:
[tex]\[ \alpha \beta = \frac{c}{a} = \frac{-3}{6} = -\frac{1}{2} \][/tex]
The product is [tex]\( \left(\frac{3}{2}\right) \times \left(-\frac{1}{3}\right) = -\frac{3}{6} = -\frac{1}{2} \)[/tex], so it matches.
So, for [tex]\( 6x^2 - 3 - 7x \)[/tex]:
- Zeroes: [tex]\( \frac{3}{2} \)[/tex] and [tex]\( -\frac{1}{3} \)[/tex]
- Sum of zeroes: [tex]\( \frac{7}{6} \)[/tex]
- Product of zeroes: [tex]\( -\frac{1}{2} \)[/tex]
In summary:
1. For [tex]\( x^2 - 2x - 8 \)[/tex]:
- Zeroes: [tex]\(4\)[/tex] and [tex]\(-2\)[/tex]
- Sum of zeroes: [tex]\(2\)[/tex]
- Product of zeroes: [tex]\(-8\)[/tex]
2. For [tex]\( 4s^2r^4 + 4s + 16 \)[/tex]:
- Zeroes: [tex]\(\left(\frac{-\sqrt{1 - 16r^4} - 1}{2r^4}, \frac{\sqrt{1 - 16r^4} - 1}{2r^4}\right)\)[/tex]
3. For [tex]\( 6x^2 - 3 - 7x \)[/tex]:
- Zeroes: [tex]\(\frac{3}{2}\)[/tex] and [tex]\(-\frac{1}{3}\)[/tex]
- Sum of zeroes: [tex]\(\frac{7}{6}\)[/tex]
- Product of zeroes: [tex]\(-\frac{1}{2}\)[/tex]
### (i) [tex]\( x^2 - 2x - 8 \)[/tex]
1. Find the zeroes:
The quadratic equation is [tex]\( x^2 - 2x - 8 = 0 \)[/tex]. To find the zeroes, we solve:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = -2 \)[/tex], and [tex]\( c = -8 \)[/tex].
Solving, we get:
[tex]\[ x = \frac{2 \pm \sqrt{4 + 32}}{2} = \frac{2 \pm 6}{2} \][/tex]
So, the zeroes are:
[tex]\[ x = \frac{2 + 6}{2} = 4 \quad \text{and} \quad x = \frac{2 - 6}{2} = -2 \][/tex]
Thus, the zeroes are [tex]\( x = 4 \)[/tex] and [tex]\( x = -2 \)[/tex].
2. Verify the relationship between the zeroes and coefficients:
- The sum of the zeroes ([tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]) of [tex]\( ax^2 + bx + c = 0 \)[/tex] should be [tex]\( -\frac{b}{a} \)[/tex]:
[tex]\[ \alpha + \beta = - \frac{b}{a} = -\frac{-2}{1} = 2 \][/tex]
Here, the sum is [tex]\( 4 + (-2) = 2 \)[/tex], so it matches.
- The product of the zeroes ([tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]) should be [tex]\( \frac{c}{a} \)[/tex]:
[tex]\[ \alpha \beta = \frac{c}{a} = \frac{-8}{1} = -8 \][/tex]
The product is [tex]\( 4 \times (-2) = -8 \)[/tex], so it matches.
So, for [tex]\( x^2 - 2x - 8 \)[/tex]:
- Zeroes: [tex]\( 4 \)[/tex] and [tex]\( -2 \)[/tex]
- Sum of zeroes: [tex]\( 2 \)[/tex]
- Product of zeroes: [tex]\( -8 \)[/tex]
### (ii) [tex]\( 4s^2r^4 + 4s + 16 \)[/tex]
1. Find the zeroes:
The quadratic equation is [tex]\( 4s^2r^4 + 4s + 16 = 0 \)[/tex].
Solving for [tex]\( s \)[/tex]:
[tex]\[ s = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 4r^4 \)[/tex], [tex]\( b = 4 \)[/tex], and [tex]\( c = 16 \)[/tex].
Solving, we get:
[tex]\[ s = \frac{-4 \pm \sqrt{16 - 256r^4}}{8r^4} = \frac{-4 \pm \sqrt{4(1 - 16r^4)}}{8r^4} = \frac{-4 \pm 2\sqrt{1 - 16r^4}}{8r^4} = \frac{-2 \pm \sqrt{1 - 16r^4}}{4r^4} \][/tex]
So, the zeroes are:
[tex]\[ s = \frac{-2 + \sqrt{1 - 16r^4}}{4r^4} \quad \text{and} \quad s = \frac{-2 - \sqrt{1 - 16r^4}}{4r^4} \][/tex]
Thus, the zeroes are:
[tex]\[ \left( \frac{-\sqrt{1 - 16r^4} - 1}{2r^4}, \frac{\sqrt{1 - 16r^4} - 1}{2r^4} \right) \][/tex]
### (iii) [tex]\( 6x^2 - 3 - 7x \)[/tex]
1. Find the zeroes:
The quadratic equation is [tex]\( 6x^2 - 3 - 7x = 0 \)[/tex]. Rearranging it to standard form, we get [tex]\( 6x^2 - 7x - 3 = 0 \)[/tex].
Here, [tex]\( a = 6 \)[/tex], [tex]\( b = -7 \)[/tex], and [tex]\( c = -3 \)[/tex].
Solving, we get:
[tex]\[ x = \frac{7 \pm \sqrt{49 + 72}}{12} = \frac{7 \pm \sqrt{121}}{12} = \frac{7 \pm 11}{12} \][/tex]
So, the zeroes are:
[tex]\[ x = \frac{7 + 11}{12} = \frac{18}{12} = \frac{3}{2} \quad \text{and} \quad x = \frac{7 - 11}{12} = \frac{-4}{12} = -\frac{1}{3} \][/tex]
Thus, the zeroes are [tex]\( x = \frac{3}{2} \)[/tex] and [tex]\( x = -\frac{1}{3} \)[/tex].
2. Verify the relationship between the zeroes and coefficients:
- The sum of the zeroes ([tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]) should be [tex]\( -\frac{b}{a} \)[/tex]:
[tex]\[ \alpha + \beta = - \frac{b}{a} = -\frac{-7}{6} = \frac{7}{6} \][/tex]
Here, the sum is [tex]\( \frac{3}{2} + \left(-\frac{1}{3}\right) = \frac{9}{6} - \frac{2}{6} = \frac{7}{6} \)[/tex], so it matches.
- The product of the zeroes ([tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]) should be [tex]\( \frac{c}{a} \)[/tex]:
[tex]\[ \alpha \beta = \frac{c}{a} = \frac{-3}{6} = -\frac{1}{2} \][/tex]
The product is [tex]\( \left(\frac{3}{2}\right) \times \left(-\frac{1}{3}\right) = -\frac{3}{6} = -\frac{1}{2} \)[/tex], so it matches.
So, for [tex]\( 6x^2 - 3 - 7x \)[/tex]:
- Zeroes: [tex]\( \frac{3}{2} \)[/tex] and [tex]\( -\frac{1}{3} \)[/tex]
- Sum of zeroes: [tex]\( \frac{7}{6} \)[/tex]
- Product of zeroes: [tex]\( -\frac{1}{2} \)[/tex]
In summary:
1. For [tex]\( x^2 - 2x - 8 \)[/tex]:
- Zeroes: [tex]\(4\)[/tex] and [tex]\(-2\)[/tex]
- Sum of zeroes: [tex]\(2\)[/tex]
- Product of zeroes: [tex]\(-8\)[/tex]
2. For [tex]\( 4s^2r^4 + 4s + 16 \)[/tex]:
- Zeroes: [tex]\(\left(\frac{-\sqrt{1 - 16r^4} - 1}{2r^4}, \frac{\sqrt{1 - 16r^4} - 1}{2r^4}\right)\)[/tex]
3. For [tex]\( 6x^2 - 3 - 7x \)[/tex]:
- Zeroes: [tex]\(\frac{3}{2}\)[/tex] and [tex]\(-\frac{1}{3}\)[/tex]
- Sum of zeroes: [tex]\(\frac{7}{6}\)[/tex]
- Product of zeroes: [tex]\(-\frac{1}{2}\)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.